THE EDUCATIONAL CLIP AND ITS EXPLOITATION FOR THE EXPOSITION OF TERM AND CONCEPT KNOWLEDGE - TVARUZKA, Vaclav (Trends in education, 2008)
This story describes conclusion of a particular research of visual structures used in a technological education. In the research there is checked an educational clip presenting conceptual knowledge. The necessity to search structures of educational clips during classwork is motivated by innovative trend, tendency to improve teaching process, simplify or accelerate bilateral communication and confirm possibilities of stimulation of pupil extasciiacutes attention by this educational construct.
Keywords: Educational clip; conceptual knowledge; technological education; communication